Methods and devices for selecting items such as data files - Clifton-Bligh, Gervase (2010)
A method is described for allowing a user to select one of a plurality of items. The user employs a device having a display area, and a joystick or a contact sensitive area. The device displays a number of regions equal to the number of items, and defines a number of sections in the angular range of the joystick, or sections within the contact sensitive area, equal to the number of items, and arranged corresponding to the arrangement of the regions of the display area. The user selects one of said items by selecting the corresponding section.